Chronic Endometritis and Antimicrobial Resistance: Towards a Multidrug-Resistant Endometritis? An Expert Opinion - Francesco Di Gennaro; Giacomo Guido; Luisa Frallonardo; Laura Pennazzi; Miriana Bevilacqua; Pietro Locantore; Amerigo Vitagliano; Annalisa Saracino; Ettore Cicinelli (Microorganisms)
Chronic endometritis (CE) is a persistent inflammatory condition of the endometrium characterized by abnormal infiltration of plasma cells into the endometrial stroma. Frequently associated with repeated implantation failure, recurrent pregnancy loss, and infertility, CE significantly impacts women’s health, contributing to conditions such as abnormal uterine bleeding and endometriosis. Treatment typically involves antibiotic therapy; however, the efficacy of these treatments is increasingly compromised by the rise of antimicrobial resistance (AMR). This paper examines the critical links between AMR and CE, proposing strategies to enhance clinical management and optimize treatment outcomes.